Project 4 : Connection - Gwangju Biennale Foundation (Gwangju Biennale Foundation, 2002)
29 Mar- 29 Jun 2002. Critical reflections on the current global situation of contemporary art. An event city created through close, interactive collaborations and diverse interventions among the artist, architect and curators.
English; Korean
Keywords: Korea; N4390-5098 Visual Arts- Exhibitions